POLA DINAMIKA AIR TANAH DI DAERAH BEKASI BERDASARKAN ANALISI RADIOISOTOP 14C - Darwin A Siregar; Satrio satrio (Jurnal Geologi dan Sumberdaya Mineral, 2009)
A study of deep groundwater dynamic pattern on the basis of radioisotope 14C analysis has been carried out in the Bekasi Â area. Some samples of deep groundwater were collected for14 C analysis. The results were plotted on the locality map concerned and a contour pattern was obtained. The pattern shows that the deep groundwater age of the area south of Bekasi is younger than those of the north and northwest area. This suggests that deep groundwater in the study area flows in the north and northwest directions. Meanwhile, Bekasi area is the recharge area. Â Keywords: Bekasi dynamic pattern, deep groundwater, 14C analysisÂ